Relationship of physical activity at older age with biomarkers of oxidative stress: a large, population-based cohort study - Schöttker, Ben; Salem, Ahmed; Schwenk, Michael; Gao, Xin; Jansen, Eugène H. J. M.; Brenner, Hermann (Medicine and science in sports and exercise, 2021)
Introduction: No population-based cohort study on the associations of physical activity with biomarkers of oxidative stress has been performed so far. Methods: The total thiol groups of serum proteins (TTP), which can be considered as a proxy biomarker for the antioxidant defense capacity of cells and the derivatives of reactive oxygen metabolites (D-ROM) serum concentration, which is mainly a biomarker of lipid peroxidation, were measured in 2572 participants of a population-based cohort study of older adults (age range, 57-83 yr), of whom 2068 had repeated measurements 3 yr later. Physical activity was assessed by a questionnaire specifically designed for the elderly. Results: In multivariable linear regression models, total physical activity was statistically significantly, inversely associated with both D-ROM concentrations measured at baseline and their 3-yr change. With respect to TTP, a nonsignificant, positive association with total physical activity was observed in the cross-sectional analysis, which was statistically significant in obese study participants, and a statistically significant interaction between physical activity and obesity was detected. However, no longitudinal association between total physical activity and changes in TTP levels was observed. The type of physical activity (sports, leisure time, or household activity) did not have a strong effect on the results. Conclusions: This first population-based cohort study suggests that regular physical activity at older age could reduce oxidative stress. With the multifold potential adverse health consequences of chronically increased, systemic oxidative stress in mind, physical activity should be intensively promoted for all older adults as a measure to prevent age-related diseases.